Cutaneous fungal infections in subjects with diabetes mellitus - S., Thilak; M., Anbumalar; Priya M., Sneha (International Journal of Research in Dermatology, 2017)
Background: Diabetes mellitus is a chronic non-communicable disease causing an increase in blood glucose levels due to an ineffectiveness or insufficiency of secreted insulin. Infections have also been shown to be the most common skin changes in diabetics. In our study we aim to assess the susceptibility of diabetics to various superficial fungal infections. We will study candidiasis, tinea versicolor and dermatophytic infections in diabetics. Methods: 400 diabetic individuals who gave consent were chosen at random from the patients attending the OPD. They were subjected to thorough clinical evaluation. Routine hematological investigations were done. FBS, PPBS, and HBA1C were done to assess diabetic control. Fungal infections were confirmed by KOH mounts. Results: Of the 400 subjects 220 were male and 180 were female. 52.5% of the subjects had some fungal infections. 55.2% of the fungal infections were candidiasis. 27.6% of the fungal infections were dermatophytic infections. 17.1% of the fungal infections were tinea versicolor infections. Conclusions: The study has analysed the epidemiology of cutaneous fungal infections in diabetics. A little over half the diabetics studied proved to have cutaneous fungal infections. Candidiasis was the most frequent form of cutaneous fungal infections accounting for 57% of the fungal infections. Dermatophytic infections were seen in 28% of infections and pityriasis versicolor for 17% of the infections. This high prevalence of cutaneous fungal infections among diabetics merits systematic screening for the same among this target group.